Chapter 6 Norwegian-Russian political relations and Barents oil and gas developments - Krivorotov, Andrey (Taylor & Francis, 2015)
The political relationship between Norway and Russia will influence the development of Barents Sea oil and gas. The state plays a decisive role in both the Norwegian and Russian parts of the sea. It does so as a regulator, through taxation, and through the national oil and gas companies, Gazprom, Rosneft, and Statoil. Thus, if the two states have a good relationship characterized by mutual trust, they can coordinate, search for complementarities, and mitigate issues that arise. Furthermore, due to the rising cost of oil and gas production in the Arctic, many oil and gas fields there may deliver small returns on investments. Scale economies brought about by coordinated development, joint infrastructure, and information sharing can tip projects from being commercially unviable to viable. But this depends on the ability and willingness of the two states to actively work together.